Improvement of Total Flavonoids from Dracocephalum moldavica L. in Rats with Chronic Mountain Sickness through 1H-NMR Metabonomics. (3rd May 2021) - Maimaiti, Atiguli; Tao, Yang; Minmin, Wang; Weiwei, Miao; Wenhui, Shi; Aikemu, Ainiwaer; Maimaitiyiming, Dilinuer
Abstract : Background . We analyzed the effects of total flavonoids from Dracocephalum moldavica L . ( D. moldavica L.) on improving chronic mountain sickness (CMS) in rats using the NMR hydrogen spectrum ( 1 H-NMR) metabonomics technology. Method . We extracted the total flavonoids of D. moldavica L with 60% ethanol reflux. A CMS model was established with 48 Sprague–Dawley (SD) rats, which were then randomly divided into six groups ( n  = 8): control group (normal saline, 0.4 mL/100 g/d, ig); model group (normal saline, 0.4 mL/100 g/d, ig); nifedipine group (nifedipine tablets, 2.7 mg/kg/d, ig); and high-, middle-, and low-dose groups of total flavonoids from D. moldavica L . (DML.H, DML.M, and DML.L, receiving total flavonoids from D. moldavica L. at 400, 200, and 100 mg/kg/d, ig, respectively). The sera of the rats in all the groups were determined, and NMR hydrogen spectrum metabolomics was analyzed. The serum contents of apolipoproteins A1 (Apo-A1) and E (Apo-E) were determined, and histopathological changes in the brain tissue of each group were observed. Results . Serum tests showed that total flavonoids from D. moldavica L. significantly increased the Apo-A1 and Apo-E levels in rats with CMS (P < 0.05 ). The results of serum metabonomics showed that total flavonoids from D. moldavica L can alleviate amino acid, energy, and lipid metabolism disorders in rats with CMS. Pathohistological examination of brain tissue showed that these flavonoids improved pathological changes, such as meningeal vasodilation, hyperemia, edema of brain parenchyma, inflammatory cell infiltration, increase in perivascular space, and increase in pyramidal cells. Conclusion . Total flavonoids from D. moldavica L. have potential therapeutic effects on CMS. The possible mechanism is the reduction of oxidative damage through the alleviation of metabolism disorder.